The Impact Of Islamic Banking On Financial Inclusion In Developing Countries: A Systematic Literature Review - Fathihani; Inngamul Wafi; Riska Rosdiana (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This literature review aims to systematically analyze and synthesize existing research on the impact of Islamic banking on financial inclusion in developing countries, with a specific focus on four Southeast Asian nations: Indonesia, Malaysia, Brunei Darussalam, and Singapore. The study seeks to identify key patterns, challenges, and opportunities in the relationship between Islamic banking development and financial inclusion outcomes. Method - The review employs a systematic literature review methodology, analyzing peer-reviewed articles, policy documents, and institutional reports published between 2013 and 2024. The analysis focuses on four key dimensions: regulatory frameworks, technological innovation, market penetration, and socio-economic impact. A structured content analysis approach was used to synthesize findings from 87 selected publications. Result - The review reveals a significant positive correlation between Islamic banking development and financial inclusion metrics across the studied countries. Malaysia demonstrates the most advanced integration of Islamic banking with financial inclusion initiatives, supported by comprehensive regulatory frameworks and technological innovation. Indonesia shows rapid growth potential but faces infrastructure challenges, while Brunei Darussalam exhibits high market penetration within a smaller market. Singapore's unique position as a regional Islamic finance hub contributes differently to financial inclusion through sophisticated product development and cross-border services. Implication - The findings suggest that successful integration of Islamic banking with financial inclusion objectives requires a holistic approach encompassing regulatory reform, technological advancement, and market development strategies. The review identifies best practices and lessons learned that can inform policy development in other developing nations seeking to leverage Islamic banking for financial inclusion. Originality - This review provides the first comprehensive cross-country analysis of Islamic banking's impact on financial inclusion in Southeast Asia, synthesizing recent empirical evidence and theoretical frameworks. It contributes to the literature by identifying patterns of successful implementation and challenges across different market contexts, offering valuable insights for policymakers and practitioners.